2019
DOI: 10.1002/cpdd.645
|View full text |Cite
|
Sign up to set email alerts
|

Ataluren Pharmacokinetics in Healthy Japanese and Caucasian Subjects

Abstract: To evaluate the potential for ethnicity‐related differences in ataluren pharmacokinetics (PK) and safety, a phase 1 single‐dose study was conducted in 48 healthy (24 Japanese and 24 Caucasian subjects), nonsmoking male volunteers who were equally divided into 3 cohorts of oral doses at 5, 10, and 20 mg/kg. Blood samples were collected until 48 hours postdose. PK results demonstrated rapid absorption of ataluren, with peak plasma levels (C max ) being attained between 0.875 and 2.5 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…DMD patients treated with drugs or other phenol-based nutraceuticals metabolized by UGT may, therefore, incur in unwanted interactions with GTE [128]. For instance, UGT1A9 is also the major enzyme that metabolizes ataluren, a novel drug recently approved for DMD to promote ribosomal read-through for patients with premature stop codon mutations [31,129]. Its metabolism could be delayed or impaired by GTE, with potential toxic effects.…”
Section: Side Effects Mechanism Of Toxicity and Interactionsmentioning
confidence: 99%
“…DMD patients treated with drugs or other phenol-based nutraceuticals metabolized by UGT may, therefore, incur in unwanted interactions with GTE [128]. For instance, UGT1A9 is also the major enzyme that metabolizes ataluren, a novel drug recently approved for DMD to promote ribosomal read-through for patients with premature stop codon mutations [31,129]. Its metabolism could be delayed or impaired by GTE, with potential toxic effects.…”
Section: Side Effects Mechanism Of Toxicity and Interactionsmentioning
confidence: 99%
“…Nonsense suppression therapy used in non-hematologic genetic diseases such as DMD and CF. Ataluren (Translarna ® ) is an approved drug for the treatment of DMD and, importantly, several Phase II/III clinical studies reported very low toxicity of ataluren even in pediatric patients aged two and older [189][190][191][192][193][194]219].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…This molecule, which can rescue expression of genes carrying UGA, UAG, or UAA nonsense mutations, has a mode of action that remains to be clarified, but might either target the A site of the ribosome as do aminoglycosides or interact directly with the stop codon to promote readthrough (Roy et al ., 2016; Tutone et al ., 2019). Even though the efficacy of this molecule seems too low for clinical development aimed at treating, for example, cystic fibrosis or Duchenne muscular dystrophy (Kerem et al ., 2014; Haas et al ., 2015), it does illustrate the need to identify readthrough molecules that might enhance the treatment of nonsense‐mutation‐related genetic diseases (Kong et al ., 2019). Among other readthrough molecules, a dipeptide‐like hydrazide antibiotic negamycin, originally purified from Streptomyces purpeofuscus , appears more potent than aminoglycosides and less toxic, as do negamycin derivatives (Arakawa et al ., 2003; Taguchi et al ., 2014; Hamada et al ., 2019) (Table 2).…”
Section: Parameters Influencing Stop Codon Readthroughmentioning
confidence: 99%